Ciliary body medulloepithelioma: four cases associated with pleuropulmonary blastoma—a report from the International Pleuropulmonary Blastoma Registry. Issue 7 (13th December 2010) - Priest, John R; Williams, Gretchen M; Manera, Ricarchito; Jenkinson, Helen; Bründler, Marie-Anne; Davis, Samuel; Murray, Timothy G; Galliani, Carlos A; Dehner, Louis P
Abstract : Background and aims: Ciliary body medulloepithelioma (CBME) is a rare embryonal ocular tumour of children under age 10 years. Pleuropulmonary blastoma (PPB) is a rare embryonal lung tumour in young children and the sentinel disease of the PPB Family Tumour and Dysplasia Syndrome, a distinctive predisposition leading to unusual dysontogenetic-dysplastic and neoplastic conditions in PPB patients and their relatives. Germline mutations of DICER1 gene, a key regulator of gene silencing, underlie this syndrome. CBME occurs with PPB. The authors' aim was to identify CBME cases associated with PPB. Methods: The authors evaluated International PPB Registry and literature PPB cases for CBME, including review of pathologic specimens. Results: Four CBME were observed among 550–600 PPB cases; three in patients and one in a parent. One CBME was clinically diagnosed; three were confirmed pathologically (one benign teratoid CBME; one benign non-teratoid CBME; one case, details not available). Conclusions: These observations suggest that CBME is a manifestation of the tumour predisposition associated with PPB. Paediatric oncologists and ophthalmologists should be aware that CBME can occur in PPB patients or their relatives and that CBME may indicate a hereditable tumour predisposition for a child or family.